Increasing the efficiency of potato breeding through marker assisted selection - general thoughts. Molecular markers for late blight resistance - when applied for breeders? - Trognitz, Bodo R.; Trognitz, Friederike Ch. (Plant Breeding and Seed Science, 2004)
Despite many breathtaking breakthroughs in the area of crop genetics and genomics, plant breeding still widely depends on the methods that had been worked out almost a century ago. This is not because commercial plant breeders are overly conservative but because the new knowledge lacks efficient and economical tools that would permit their application in practice. Breeders desire supporting technologies that would facilitate laborious and time-consuming screening in the field and laboratory. In particular, resistance screening often cannot be performed satisfactorily as the necessary disease pressure and appropriate pathogen populations may be unavailable. In potato breeding, specific and often complex resistances need to be developed, at the same time maintaining high levels of quality and culinary characteristics. Therefore, it is worthwhile to revisit the facts that comprise the progress in genetics of disease resistance and to analyze current technologies of genotyping and marker assisted selection, with the objective to detect those parameters that limit the efficiency of methods for commercial application. Selection in potato for resistance to late blight will be highlighted as an example. Maps, genes and markers for resistance have been identified – how universal are they? Single genes and quantitative trait loci for race-specific and race non-specific resistance are known – how efficient is their use? Marker technologies based on polymerase chain reaction and DNA hybridization have been developed that are far more efficient than first-generation technologies – is their use in commercial breeding economical? By discussing these issues concepts will emerge that help to pave the way for marker assisted selection (MAS) in potato breeding. The most important parameters required for economical MAS include to have a clear idea of the traits to be selected for, to use proven, reliable markers, to have in place a robust system for the collection and management of DNA samples, and to use technologies whose total cost is below or equal to the cost of the conventional methods. The most striking advantages of MAS are that a breeder will obtain more information than by conventional methodology, the information will be more precise, field labour can be saved and in that way the breeding process will be intensified. The implementation of the new technology could lead to even closer collaboration of breeders and scientists. Possible disadvantages include the relative increase of laboratory and computer work within the breeding program, and possibly higher costs during the implementation phase of the new technology.